Underlying mechanisms and chemical/biochemical therapeutic approaches to ameliorate protein misfolding neurodegenerative diseases - Hekmatimoghaddam, Seyedhossein; Zare‐Khormizi, Mohamad Reza; Pourrajab, Fatemeh (BioFactors (Oxford), 2017)
Protein misfolding and inclusion body formations are common events in neurodegenerative diseases characterized by deposition of misfolded proteins inside or outside of neurons, and are commonly referred to as “protein misfolding neurodegenerative diseases” (PMNDs). These phenotypically diverse but biochemically similar aggregates suggest a highly conserved molecular mechanism of pathogenesis. These challenges are magnified by presence of mutations that render individual proteins subject to misfolding and/or aggregation. Cell proteostasis network and molecular chaperoning are maintaining cell proteome to preserve the protein folding, refolding, oligomerization, or disaggregation, and play formidable tasks to maintain the health of organism in the face of developmental changes, environmental insults, and rigors of aging. Maintenance of cell proteome requires the orchestration of major pathways of the cellular proteostasis network (heat shock response (HSR) in the cytosol and the unfolded protein response (UPR) in the endoplasmic reticulum). Proteostasis responses culminate in transcriptional and post‐transcriptional programs that up‐regulate the homeostatic mechanisms. Proteostasis is strongly influenced by the general properties of individual proteins for folding, misfolding, and aggregation. We examine a growing body of evidence establishing that when cellular proteostasis goes awry, it can be reestablished by deliberate chemical and biological interventions. We first try to introduce some new chemical approaches to prevent the misfolding or aggregation of specific proteins via direct binding interactions. We then start with approaches that employ chemicals or biological agents to enhance the general capacity of the proteostasis network. We finish with evidence that synergy is achieved with the combination of mechanistically distinct approaches to reestablish organ proteostasis. © 2016 BioFactors, 43(6):737–759, 2017